2021
DOI: 10.3390/jcm10122715
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine/Cytokine Levels Correlate with Organ Involvement in PR3-ANCA-Associated Vasculitis

Abstract: Background: ANCA-associated vasculitis (AAV) is a rare small vessel disease characterized by multi-organ involvement. Biomarkers that can measure specific organ involvement are missing. Here, we ask whether certain circulating cytokines and chemokines correlate with renal involvement and if distinct cytokine/chemokine patterns can differentiate between renal, ear/nose/throat, joints, and lung involvement of AAV. Methods: Thirty-two sets of Birmingham vasculitis activity score (BVAS), PR3-ANCA titers, laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…31,32 Patients with ECGN with high platelet turnover and/or thrombocytosis were also described. 33,34 Importantly, we found as other did 35 that the serum level of TPO increased in patients with active GPA-K 1 and contributed to predict response to treatment. TPO is hence a valuable biomarker in this context.…”
Section: Discussionsupporting
confidence: 66%
“…31,32 Patients with ECGN with high platelet turnover and/or thrombocytosis were also described. 33,34 Importantly, we found as other did 35 that the serum level of TPO increased in patients with active GPA-K 1 and contributed to predict response to treatment. TPO is hence a valuable biomarker in this context.…”
Section: Discussionsupporting
confidence: 66%
“…Recent publications have demonstrated that CXCL9 and CXCL16 are increased in AAV compared to controls 23 , 25 . In addition, a distinct chemokine levels in the circulation was also identified in PR3-ANCA AAV according to organ involvement 21 , and a prognostic role of CCL18 in ANCA-associated glomerulonephritis has been also described 22 , with the disease activity status predicting potential of CCR8, CXCL2, CXCL13, CCL5, CCL20, CCL22 suggested in AAV 24 , 26 29 . On the other hand, investigation of CX3CL1 in patients with MPA and GPA revealed increased level in the periphery compared to controls, with relationship present with BVAS and active disease, respectively 30 , 31 .…”
Section: Discussionmentioning
confidence: 94%
“…Meanwhile, several chemokines were revealed as potential markers of disease severity in SLE and predicted kidney involvement, implying that chemokines could be biological markers reflecting inflammation at the systemic and local levels in AIDs 19 , 20 . Similarly, there are investigations that assessed the role of chemokines expression in the circulation in AAV and its subtypes, showing association with clinical phenotypes or disease status 21 31 . Considering the increasing comprehension of chemokines in the development of AIDs, there is a necessity for enhanced insight into chemokines among patients with MPA/GPA; however, few studies have been conducted to date.…”
Section: Introductionmentioning
confidence: 99%